Strategi Komunikasi Risiko COVID-19 Program PKMM-CBA LPBI NU untuk Mendorong Perilaku Pencegahan COVID-19 - Yusuf, M. Ali; Yuliasari, Ika; Komalawati, Euis (LUGAS Jurnal Komunikasi, 2024)
Apart from implementing appropriate strategies to increase understanding of the risks of COVID-19 and how to reduce the risks, COVID-19 communication risk requires various efforts to foster public interest and willingness to carry out COVID-19 risk reduction behaviors by implementing health protocols and vaccination.By using the Extended Parallel Process Model (EPPM) and Theory of Planned Behavior (TPB), this research explores and analyzes the risk communication strategy of the PKMM-CBA LPBI NU program in increasing public understanding and awareness of the risks of COVID-19 and efforts to reduce them in Metatu & Punduttrate Village, Benjeng District, Gresik Regency, East Java Province, accompanied by disclosure of factors that encourage people to take actions to reduce risks.The research results show that in addition to appropriate risk communication strategies, there is a need to provide facilities and support to foster public interest and willingness to comply with health protocols aswell as community social awareness to remind each other about compliance with COVID-19 health protocols and also vaccination.